PENYEDIAAN FASILITAS UMUM TAMAN BERMAIN DI LINGKUNGAN KOMPLEK SAWANGAN ELOK KECAMATAN BOJONGSARI KOTA DEPOK - Ahmad Muhajir; Muhamad Lutfi (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2024)
Activities in public open spaces are most often carried out by children. Scientifically playing activities are very supportive of children's development such as learning and adapting to their sensory abilities. One of the play spaces that can be used by children is in public spaces, especially in residential areas. Many children do not have a yard to play in, so a playground is very important and is often the only place for children to play. The park is part of a green open space that mainly functions as a pollutant reducer and rainwater absorber. In its development, the use of the park has turned into a place that can accommodate residents. The Sawangan Elok Complex is one of the complexes located in Bojongsari District, Durenseribu Village, Depok City, which does not yet have public playground facilities for community activities, namely children's play activities and sports, especially in a settlement. For this reason, it is necessary to know what criteria must be met in presenting children's play activities and exercising in a playground to reduce boredom maintain health and increase the body's immunity so that it is not easily exposed to the corona virus during a pandemic like now. These criteria are used as the basis for providing a playground so that the use of the park can be felt directly by the surrounding community.